Hydrogen nanobubble water coordinates functional microbes and metabolic genes in high-solid co-digestion of swine manure and Paulownia leaf litter for enhanced methanogenesis - Yujie Fan; Yuqiao Wang; Dawei Guo; Mingxuan Li; Xiaojing Yang; Ziwen Zhao (Bioresource Technology, 2026)

The fermentative product from Bacillus siamensis HU603 (6′-phospho macrolactin B) inhibits Micropterus salmoides rhabdovirus infection in vitro and in vivo - Xinhui Tong; Yan Zhou; Qianhao Shao; Huan Qi; Xutin Guan; Shiwen Sun; Ningyu Zhu; Fan Zhou; Dawei Song; Jidong Wang (Fish & Shellfish Immunology, 2026)

Mitigating ammonia inhibition in anaerobic digestion of swine manure using hydrogen nanobubble water acclimation: Multi-omics insights - Yujie Fan; Dawei Guo; Yuqiao Wang; Mingxuan Li; Xiaojing Yang; Ziwen Zhao (Bioresource Technology, 2026)

Insights for optimizing campus tree species from children's thermal and physiological responses during transitional seasons - Jiahao Yang; Tongye Guo; Yini Fan; Xinyi Luo; Shaolin Gan; Dawei Xia; Xiwen Feng (Energy and Buildings, 2026)

High-temperature behavior of FeTiO3 and MgTiO3: in-situ synchrotron X-ray diffraction study - Kai Wang; Jingui Xu; Shijie Huang; Shanrong Zhang; Qifa Zhong; Wei Zhao; Dawei Fan (Physics and Chemistry of Minerals, 2026)

Synergistic mechanisms of norfloxacin degradation and fouling mitigation in an electrocoagulation-ultrafiltration system - Jiarou Jin; Luoyun Xu; Shujuan Meng; Meng Zhang; Lingling Chen; Wenhong Fan; Dawei Liang; Linyan Yang; Wenda Oh (Chemical Engineering Journal, 2026)

Performance of tree canopy cover in mitigating future extreme heat across local climate zones: A case study of Guangzhou - Yini Fan; Yukai Zou; Dawei Xia; Xiaolin Yang; Tongye Guo; Jiahao Yang; Xiang Zhang (Urban Climate, 2026)

Equation of state and structural variations of synthetic forsterite-fayalite solid solution by single-crystal X-ray diffraction - Zhilin Ye; Jingui Xu; Dongzhou Zhang; Weiyi Liu; Wenge Zhou; Dawei Fan (Physics and Chemistry of Minerals, 2026)

Transport stress accelerated the deterioration of physicochemical and microbiological quality in grass carp (Ctenopharyngodon idellus) muscle associated with apoptosis mechanism - Min Shan; Minping Wei; Lei Gan; Dawei Yu; Qin Cen; Zhiling Chen; Lingyan Huang; Jing Fan; Huaimao Tie; Xuefeng Zeng (Aquaculture, 2026)

Sodium sulfate recovery from red mud by selective de-alkalization using ferric sulfate solution and its regeneration - Zhenquan Yang; Hannian Gu; Zehai Li; Dawei Fan; Hanjie Wen (Hydrometallurgy, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Combined effects of polystyrene micro-/nano-plastics and imidacloprid on Gut–Brain axis and neurotoxicity in juvenile Carassius auratus - Xinzi Guo; Lin Peng; Zhaoxuan Zhu; Shuocheng Fan; Jiasen Feng; Xingxing Fang; Dawei Guo; Ping Yang (Journal of Environmental Management, 2026)

Crystallization of REE phases within La-Na-(Ca)-Cl-(F)-C-H-O systems - Jingui Xu; Qifa Zhong; Wei Zhao; Dongzhou Zhang; Li Zhou; Yi Zhou; Wei Zhang; Wenge Zhou; Dawei Fan (Chemical Geology, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Pressure-temperature stability and equation of state of staurolite: Implications for the water transport during cold slab subduction - Shijie Huang; Jingui Xu; Dongzhou Zhang; Shanrong Zhang; Yufeng Liu; Yikui Liang; Zimo Li; Wenge Zhou; Dawei Fan (Lithos, 2026)

Breaking CO2 reduction scaling relations via heterogeneous B/N coordination environments in single-atom catalysts - Huiwen Zhu; Zeyu Guo; Dawei Lan; Shuai Liu; Gang Yang; Fan Wang; Xiang Luo; Jiahui Yu; Tao Wu (Chemical Engineering Journal, 2026)

SSPP: a Novel Flood Probabilistic Forecasting Model Based on Synergistic Seq2Seq Framework and Peak-Enhanced Loss Function - Chang Chen; Dawei Zhang; Fan Wang; Xin Qi; Kang Zheng; Liyun Xiang (Water Resources Management, 2026)

Inconsistent capacity of potential HONO sources to enhance secondary pollutants: Evidence from WRF-Chem modeling - Jingwei Zhang; Haiyan Ran; Yu Qu; Chaofan Lian; Weigang Wang; Yusheng Zhang; Feixue Zheng; Xiaolong Fan; Dawei Lu; Chao Yan; Kaspar R. Daellenbach; Zhiqiang Ma; et al. (Journal of Environmental Sciences, 2025)

Multi-omics profiling delineates reheating-modality-driven flavor divergence in Yuxiang shredded pork - Xuan Wang; Shaoran Shi; Xiaomeng Wu; Shuang Bi; Fan Yang; Xiuli Du; Youyou Cheng; Jingguang Li; Yunfeng Zhao; Dawei Chen (Food Chemistry, 2025)

CuFe2O4@T-COF nanosphere-mediated biosensing platform based on DNA walker signal amplification strategy for ultrasensitive HPV detection - Zhen Yu; Yan Zhang; Dongquan Leng; Tingting Wu; Si-Jia Ge; Dawei Fan; Hongmin Ma; Yu Du; Qin Wei (Chemical Engineering Journal, 2025)

Multifunctional Au(I)-based AIEgens for the visualization and treatment of invasive fungal infections - Jiawei Zhou; Yizhi Fan; Yajuan Guan; Yiliang Qin; Dawei Liang; Shuangling Deng; Kaihui Shi; Yongyu Rui; Lei Zheng; Jing Zhang (Chemical Engineering Journal, 2025)

CeNEP: A general-purpose machine learning interatomic potential for cementitious materials - Fengzijun Pan; Guangyao Li; Jiaqiu Xu; Zuhao Wang; Zepeng Fan; Ai Zhang; Dawei Wang (Chemical Engineering Journal, 2025)

Rare constituents of the nasal microbiome contribute to the acute exacerbation of chronic rhinosinusitis - Yunfan Zhang; Fan Yuan; Zheng Liu; Xiaoxi Huang; Junsheng Hong; Feifan Chang; Dawei Wu (Inflammation Research, 2025)

Multistability and synchronization of fractional-order memristor-coupled tabu learning neurons model - Dawei Ding; Siqi Chen; Zongli Yang; Xinyue Xu; Jin Fan; Haifei Zhu; Xiang Liu (Cognitive Neurodynamics, 2025)

Recycling solid wastes into asphalt mastics for low-carbon pavements: Performance investigation and environmental impact assessment - Jiaqiu Xu; Zhaojie Chen; Fuliao Zou; Zhen Leng; Zepeng Fan; Guoyang Lu; Dawei Wang (Journal of Cleaner Production, 2025)

Unexpected benefits of agricultural greenhouses in mitigating ozone pollution on crop yields in China - Jingwei Zhang; Yuanqi Huang; Xiaoye Tong; Hailin Wu; Haiyan Ran; Wenxuan Fan; Yuanzhe Li; Shijing Dong; Shengsen Zhou; Jiangping Liu; Dawei Lu; Huizhi Liu; et al. (Atmospheric Environment, 2025)

Optimal stocking density enhances culture performance for all‑male culture of Chinese mitten crab Eriocheir sinensis - Guangbao Zhang; Chenwei Fan; Virakbot Hou; Zhijie Zhou; Di Kong; Dawei Zhao; Xugan Wu (Aquaculture International, 2025)

Obtaining phosphorus concentrate from phosphate ore flotation tailings after Ca and Mg recovery using formic acid leaching - Guiyong Zhou; Ning Wang; Hannian Gu; Dawei Fan; Hanjie Wen (Minerals Engineering, 2025)

Gas recovery and flowback in trans-coal-limestone fracture: An in-situ wettability microscale visualization insight - Jicheng Zhang; Dawei Lv; Dawei Yin; Xiaoyang Zhang; Xuelong Li; Kunkun Fan (Gas Science and Engineering, 2025)

Remarkable energy storage performance in lead-free tungsten bronze ferroelectrics for high temperature applications - Muhammad Fahad Riaz; Fayaz Hussain; Ali Dad Chandio; Zeshan Javed; Wenfeng Yue; Zhenhao Fan; Yuxiao Du; Bingsen Wang; Mohammad Abu Abdeen; Gulmurza Abdurakhmanov; Adil Alshoaibi; Yasemin Tabak; et al. (Chemical Engineering Journal, 2025)

Archaeogenetic analysis sheds light on genomic substructure and kinship practices of Xianbei nobles from the Yihe Nur site - Jiashuo Zhang; Fan Zhang; Youyang Qu; Mingjie Suo; Guodong Song; Yongzhi Chen; Dawei Cai (Archaeological and Anthropological Sciences, 2025)

Wind-tide modulated net ecosystem metabolism in a Changjiang River Estuary aquaculture zone during mid-autumn - Di Wu; Kui Wang; Guoquan Wang; Qinglin Mu; Wei Fan; Dawei Xu (Marine Environmental Research, 2025)

Urban-industrial synergies in Sustainability: Evaluating the Co-processing of MSWI fly ash in industrial kilns from environmental and economic perspectives - Run Shi; Fan Fei; Xuguang Wang; Dawei Liu; Shuang Wu; Junwei Bai; Yan Zhang; Wei Su; Rongrong Lei; Hao Wang; Hongzhi Ma (Journal of Cleaner Production, 2025)

Quorum sensing enhances microbial resistance to substrate toxicity during anaerobic caproate production - Jihua Zhao; Hongzhi Ma; Fan Su; Yichan Liu; Chengxuanyuan Liu; Yong Liang; Shuang Wu; Juncheng Song; Dawei Liu; Xingzhao Chen; Xiaobin Yang; Qunhui Wang; et al. (Chemical Engineering Journal, 2025)

Piezo/photo-catalytic nano-actuators modulating mechanical force for mechanosensitive anti-tumor immunotherapy - Cong Cong; Xuejiao J. Gao; Fei Ye; Xuwu Zhang; Yuchu He; Zhenhe Ma; Wenkang Tu; Weili Xue; Kelong Fan; Dawei Gao (Chemical Engineering Journal, 2025)

Spatiotemporal variation characteristics and the possible causes of groundwater storage based on GRACE in the Huai River Basin, China - Bin Wu; Jingcai Wang; Fan Li; Dawei Zhu; Jiao Pan; Jiaolong He; Wenyue Wang (Natural Hazards, 2025)

Equation of state of FeTiO3 and MgTiO3 by in-situ synchrotron X-ray diffraction at high pressures - Kai Wang; Jingui Xu; Shanrong Zhang; Qifa Zhong; Wei Zhao; Dawei Fan (Physics and Chemistry of Minerals, 2025)

Emission characteristics of indoor HONO from residential natural gas cooking stoves in a household in Kunming, China - Hailin Wu; Haiyan Ran; Shijing Dong; Lingling Li; Jiangping Liu; Wenxuan Fan; Dawei Lu; Jingwei Zhang; Junling An (Journal of Hazardous Materials, 2025)

Microwave irradiation benefits fructan degradation in sourdough steamed cake by tunning the β-fructosidase FosE-substrate interaction - Xiaoyue Ying; Yuan Tao; Yuan Yuan; Dawei Ni; Wenli Zhang; Bowen Yan; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Food Chemistry, 2025)

Microfluidic diagnostics: Evolution of gas critical paths based on dynamic alterations of cleats wettability - Jicheng Zhang; Dawei Lv; Jon Jincai Zhang; Xiaoyang Zhang; Haiyang Yu; Xuelong Li; Kunkun Fan (Chemical Engineering Journal, 2025)

Incidence, risk factors, and prognosis of hospitalized mechanical eye injuries in China: data from China Ocular Trauma Study (COTS) 2021–2023 - Han Han; Yongjie Chen; Gao Si; Guowei Huang; Jiayi Song; Wenfang Zhang; Danyan Liu; Jie Zhong; Xuemin Jin; Dawei Sun; Shenwen Liu; Yanming Huang; et al. (Science Bulletin, 2025)

Enhanced double-exchange interactions enable the Co and Mn co-doped zinc ferrite rapid and efficient removal of tetracycline - Yuqiu Fan; Dawei Liu; Haipeng Wan; Xingyu Liu; Jun Wang; Kun Xiong (Journal of Environmental Chemical Engineering, 2025)

A novel flood forecasting model based on TimeGAN for data-sparse basins - Chang Chen; Fan Wang; Zhongxiang Wang; Dawei Zhang; Liyun Xiang (Stochastic Environmental Research and Risk Assessment, 2025)

Incremental Learning with Dynamic Adaptive Elastic Weight Consolidation for Adaptive, Scalable, and Generalizable User-Defined Behavior Recognition and Analysis of Cetacean and Pinniped Species - Shih-Pang Tseng; Shen-Hang Chu; Jhing-Fa Wang; Dawei Tao; I-Fan Jen (Journal of Marine Science and Engineering, 2025)
Traditional animal behavior recognition models require extensive labeled datasets and frequent retraining, limiting their adaptability across species and environments. Additionally, existing systems rely on predefined behavior categories, making it difficult for researchers to customize recognition models to specific behavioral patterns relevant to their studies. Different research fields, such as animal welfare monitoring, conservation, and behavioral ecology, often require distinct behavior classifications, yet current systems lack the flexibility to accommodate these varying needs. This study aims to develop an expandable and user-driven animal behavior recognition system utilizing DeepLabCut for pose estimation and a BiLSTM-based classification model. By integrating Dynamic Adaptive Elastic Weight Consolidation (DA-EWC), the system enables incremental learning, allowing new behaviors to be added with minimal annotation while preserving previously learned behaviors. The proposed system is trained on dolphin behavior datasets using DeepLabCut for keypoint extraction and a BiLSTM model for sequence classification. Additionally, a user-friendly interface is implemented to facilitate behavior annotation and efficient model updates. The proposed system achieves 96.5% accuracy in behavior classification, surpassing conventional models such as Faster R-CNN. Compared to standard EWC, DA-EWC maintains an average of 8.3% higher accuracy when incorporating new behaviors. Furthermore, the system reduces annotation efforts by 9.3%, enabling users to expand behavior categories efficiently. This expandable behavior recognition system significantly enhances adaptability and efficiency in animal behavior monitoring. By supporting user-driven incremental learning, it provides a scalable solution for behavior analysis across different research domains, addressing the need for customizable and evolving behavior classification.

Novel competitive photoelectrochemical sensor array based on ZnIn2S4/CdS heterojunction for highly sensitive detection of dibutyl phthalate in the environment - Ling Wang; Qingfang Guo; Yunfei Zhang; Guangyue He; Huan Wang; Hongmin Ma; Dan Wu; Dawei Fan; Qin Wei (Chemical Engineering Journal, 2025)

Effect of Molecular Weight of Fluorescent Dyes on DNA Separation by Capillary Electrophoresis - Yuqing Xu; Xin Chen; Shuaiqiang Fan; Ting Zhang; Bo Yang; Zhenqing Li; Shintaro Yamaguchi; Dawei Zhang (Journal of Fluorescence, 2025)

Exploring novel antioxidant cyclic peptides in corn protein hydrolysate: Preparation, identification and molecular docking analysis - Hongcheng Liu; Hongxiu Fan; Xu Teng; Tong Sun; Shanshan Zhang; Nan Wang; Xu Zhang; Tingting Liu; Yanrong Zhang; Dawei Wang (Food Chemistry, 2025)

Regulation of ROS balance in the tumor microenvironment achieves reversal of immune suppression and deep penetration of nanomedicines - Zichuang Xu; Rongrong Fan; Xuhao Zhang; Yufei Guo; Sen Tan; Yifei Li; Yaqian Yan; Jiajun Gao; Weili Xue; Desong Wang; Dawei Gao (Chemical Engineering Journal, 2025)

Long-term effects of nitrogen fertilization and Bradyrhizobium inoculation on diazotrophic community structure and diversity in soybean cultivation - Wanling Wei; Mingchao Ma; Xin Jiang; Fenliang Fan; Fangang Meng; Fengming Cao; Huijun Chen; Dawei Guan; Li Li; Jun Li (Applied Soil Ecology, 2025)

An ultrasensitive ECL immunosensor with a dual signal amplification strategy using AuNPs@GO@SmMoSe2 and Gd2(MoO4)3 for estriol detection - Romana Manzoor; Aniqa Sehrish; Hanyu Wang; Huan Wang; Dawei Fan; Xuejing Liu; Dan Wu; Qin Wei (Analytica Chimica Acta, 2025)

Detection of Ginkgo biloba seed defects based on feature adaptive learning and nuclear magnetic resonance technology - Shuaishuai Zhao; Maocheng Zhao; Liang Qi; Dawei Li; Xiwei Wang; Zhong Li; Min Hu; Kaixuan Fan (Journal of Plant Diseases and Protection, 2024)

Response of bottom dissolved oxygen reduction to net ecosystem production observed by a wave-driven profiler in the Changjiang River Plume - Di Wu; Kui Wang; Wei Fan; Qicheng Meng; Feng Zhou; Minhui Zheng; Dawei Xu (Marine Environmental Research, 2024)

Mechanism of Mettl14 regulating AIM2 inflammasome activation and neuronal apoptosis and pyroptosis in spinal cord injury by mediating PPARγ m6A methylation - Fan Wu; Liqun Li; Zhigang Li; Dabiao Zhou; Zhihui Huang; Dawei Sang; Chizi Hao (Journal of Physiology and Biochemistry, 2024)

Optimization framework for daylight and thermal environment of retractable roof natatoriums based on generative adversarial network and genetic algorithm - Zhongqi Yu; Xinyi Ge; Zhaoxiang Fan; Yihang Zhou; Dawei Lin (Energy and Buildings, 2024)

Integration of membrane bioreactor with a weak electric field: Mitigating membrane fouling and improving effluent quality targeting low energy consumption - Bihui Niu; Meng Zhang; Shujuan Meng; Zhongyuan Mao; Dawei Liang; Wenhong Fan; Linyan Yang; Zhekang Dong; Yuan Liao; Jianyou Wang; Yu Liu (Chemical Engineering Journal, 2024)

One step synthesis of a novel Co-doped UiO-66 adsorbent for superior adsorption of organic dyes from wastewater - Dawei Lan; Huiwen Zhu; Jianwen Zhang; Fan Wang; Yueying Zheng; Zeyu Guo; Gang Yang; Mengxia Xu; Tao Wu (Process Safety and Environmental Protection, 2024)

Effect of aluminum ions on the change in fouling ability of foulants: Insights from the transparent exopolymer particles formation - Jiarou Jin; Yue Li; Dawei Liang; Wenhong Fan; Linyan Yang; Qian Zhao; Meng Zhang; Wenxiang Zhang; Shujuan Meng (Journal of Water Process Engineering, 2024)

A novel photoelectrochemical biosensing platform utilizing dual Type-II Bi2O3/CdLa2S4/Bi2S3 ternary heterojunctions as signal transduction materials and Cu2O nanosphere as a sensitizer for CA15-3 detection - Yong Hao; Yingying Zhang; Xiaodi Zhu; Jingui Chen; Na Song; Huan Wang; Nuo Zhang; Dawei Fan; Hongmin Ma; Qin Wei; Huangxian Ju (Chemical Engineering Journal, 2024)

Crystal structure of calcite-type Ca1–xMnxCO3 solid solution by X-ray diffraction and Raman spectroscopy - Shanrong Zhang; Wen Liang; Mengzeng Wu; Qifa Zhong; Dawei Fan (Physics and Chemistry of Minerals, 2024)

Magnetic photoelectrochemical sensor array utilizing addressing sensing strategy for simultaneous detection of amyloid-β 42 and microtubule-associated protein tau - Shuo Zhang; Yunfei Zhang; Huan Wang; Yaoguang Wang; Hongmin Ma; Dan Wu; Zhong Feng Gao; Dawei Fan; Xiang Ren; Qin Wei (Analytica Chimica Acta, 2024)

New insights into estimation of bioavailable inorganic phosphorus in natural coastal seawater - Hong Wei; Dawei Pan; Yan Liang; Xia Fan; Guowei Gai (Science of The Total Environment, 2024)

Natural resource efficiency and green economy: Key takeaways on clean energy, globalization, and innovations in BRICS countries - Lulu Fan; Dawei Wang (Resources Policy, 2024)

Anthropogenic influence has significantly affected snowfall changes in Eurasia - Wenqing Lin; Huopo Chen; Weiqi Wang; Dawei Zhang; Fan Wang; Wuxia Bi (Atmospheric Research, 2024)

Ternary electrochemiluminescence quenching effects of CuFe2O4@PDA-MB towards self-enhanced Ru(dcbpy)32+ functionalized 2D metal-organic layer and application in carcinoembryonic antigen immunosensing - Xiang Ren; Zuoxun Xie; Huan Wang; Lijun Wang; Zhongfeng Gao; Hongmin Ma; Nuo Zhang; Dawei Fan; Qin Wei; Huangxian Ju (Analytica Chimica Acta, 2024)

Livestock greenhouse gas emission and mitigation potential in China - Dawei He; Xiangzheng Deng; Xinsheng Wang; Fan Zhang (Journal of Environmental Management, 2023)

Ancient DNA sheds light on the origin and migration patterns of the Xianbei confederation - Dawei Cai; Ying Zheng; Qingchuan Bao; Xiaonong Hu; Wenhu Chen; Fan Zhang; Jianen Cao; Chao Ning (Archaeological and Anthropological Sciences, 2023)

Thermal expansivity of geikielite and ilmenite utilizing in-situ synchrotron X-ray diffraction at high temperature - Jiamei Song; Dawei Fan; Shijie Huang; Shanrong Zhang; Mengzeng Wu; Wei Chen; Wenge Zhou (Acta Geochimica, 2023)

Development of boiling flow pattern map and heat transfer correlation of R32-oil mixture inside a horizontal micro-fin tube - Guang Li; Dawei Zhuang; Liyi Xie; Guoliang Ding; Bao Yue; Bo Fan; Hao Zhang; Yanpo Shao (International Journal of Refrigeration, 2023)

Controlled synthesis of Fe3O4/MnO2 (3 1 0)/ZIF-67 composite with enhanced synergetic effects for the highly selective and efficient adsorption of Cu (II) from simulated copperplating effluents - Fan Wang; Yueying Zheng; Xinggang Wei; Dawei Lan; Jintao Zhu; Yingjie Chen; Ziquan Wo; Tao Wu (Environmental Research, 2023)

Recycling waste fiber-reinforced polymer composites for low-carbon asphalt concrete: The effects of recycled glass fibers on the durability of bituminous composites - Qilin Yang; Zepeng Fan; Xuan Yang; Lifeng Hao; Guoyang Lu; Elham H. Fini; Dawei Wang (Journal of Cleaner Production, 2023)

Guest molecule optimum aggregation hypothesis and optimal concentrations for energy storage from the perspective of hydrate phase change-induced liquid layer - Fan Wang; Yuan Lv; Xinran Xia; Lizhong Yang; Dawei Guan; Chuanxiao Cheng; Wenfeng Hu; Lunxiang Zhang; Alessandro Romagnoli; Jiafei Zhao; Yongchen Song (Journal of Cleaner Production, 2023)

Reproducible Abnormalities and Diagnostic Generalizability of White Matter in Alzheimer’s Disease - Yida Qu; Pan Wang; Hongxiang Yao; Dawei Wang; Chengyuan Song; Hongwei Yang; Zengqiang Zhang; Pindong Chen; Xiaopeng Kang; Kai Du; Lingzhong Fan; Bo Zhou; et al. (Neuroscience Bulletin, 2023)

Porphyrin-based metal-organic frameworks enhanced electrochemiluminescence (ECL) by overcoming aggregation-caused quenching: A new ECL emitter for the detection of trenbolone - Beibei Wang; Lu Zhao; Yuyang Li; Xuejing Liu; Dawei Fan; Dan Wu; Qin Wei (Analytica Chimica Acta, 2023)

An innovative and efficient hydrogen peroxide-citric acid pretreatment of bamboo residues to enhance enzymatic hydrolysis and ethanol production - Fanyang Meng; Jing Fan; Fei Cui; Haiyan Yang; Zhengjun Shi; Dawei Wang; Jing Yang (Bioresource Technology, 2023)

Type-I heterojunction destruction by In situ formation of Bi2S3 for split-type photoelectrochemical aptasensor - Xue Dong; Hanyu Wang; Xiang Ren; Hongmin Ma; Dawei Fan; Dan Wu; Qin Wei; Huangxian Ju (Analytica Chimica Acta, 2023)

Facile preparation of poly-(styrene-co-maleic anhydride) encapsulated Iridium(III) complexes as highly efficient electrochemiluminescence indicators for sensitive immunoassay of CYFRA 21-1 - Yunhui Hua; Xiang Ren; Hongmin Ma; Dan Wu; Xianzhen Song; Huan Wang; Lei Yang; Dawei Fan; Qin Wei (Analytica Chimica Acta, 2023)

The Changjiang River plume shifts from carbon source to sink when net community production exceeds a threshold in early autumn - Di Wu; Jianfang Chen; Kui Wang; Xiaobo Ni; Dewang Li; Dingyong Zeng; Wei Fan; Dawei Xu (Science of The Total Environment, 2023)

Rational design and reduction kinetics of efficient Ce-Co oxygen carriers for chemical looping reforming of methane - Weixiang Zhang; Lina Zhang; Sijia Pei; Jiarui Wang; Dawei Liu; Xiaoxun Ma; Maohong Fan; Long Xu (Fuel, 2023)

A hybrid shallow water approach with unstructured triangular grids for urban flood modeling - Weiqi Wang; Wenjie Chen; Guoru Huang; Jiahong Liu; Dawei Zhang; Fan Wang (Environmental Modelling & Software, 2023)

A novel method for evaluating the durability and environmental pollution of road markings on asphalt pavement - Dawei Wang; Xuan Yang; Xiangyu Chu; Yulin He; Zepeng Fan; Chao Xing; Pengfei Liu (Journal of Cleaner Production, 2023)

Bisthiourea immobilized UiO-66-NH2 supported Fe2O3 nanoparticles to accelerate dual centers Fenton-like reaction - Xu Huang; Xiaohu Fan; Aimin Li; Yechao Tian; Dawei Li (Science of The Total Environment, 2023)

Hypergolic ignition induced by head-on collision of bi-propellant droplets: Monoethanolamine-based fuel and hydrogen peroxide - Dawei Zhang; Dehai Yu; Yueming Yuan; Peng Zhang; Xuejun Fan (Fuel, 2023)

Experimental Investigation on the Slip Nucleation of Laminated Shale During Fracture Propagation - Lei Chen; Guangqing Zhang; Min Zhang; Chaohao Zhai; Zongyang Fan; Jianlin Zhao; Dawei Zhou; Shiyuan Li (Rock Mechanics and Rock Engineering, 2023)

Polyacrylic acid/polyethylene glycol hybrid antifouling interface for photoelectrochemical immunosensing of NSE based on ZnO/CdSe - Dawei Fan; Jing Luo; Zhengxing Gong; Huan Wang; Hongmin Ma; Dan Wu; Qin Wei; Huangxian Ju (Analytica Chimica Acta, 2023)

Long-term over-the-horizon microwave channel measurements and statistical analysis in evaporation ducts over the Yellow Sea - Shuwen Wang; Kunde Yang; Yang Shi; Hao Zhang; Fan Yang; Dawei Hu; Guoyu Dong; Yihang Shu (Frontiers in Marine Science, 2023)
Maritime high-speed over-the-horizon wireless communication is realizable through evaporation ducts. Detailed measurement, analysis, and modeling of duct channels are essential for application of this communication technique. In this paper, X-band electromagnetic (EM) wave propagation systems were developed and deployed for a 133-km over-the-horizon microwave link in coastal areas of the Yellow Sea. The propagation length was 7.7 times the line-of-sight length. Measurement results including the path loss (PL) and meteorological data were obtained during a 54-day period in autumn 2021. The long-term channel results were analyzed on the basis of statistical analysis and model simulations. Results showed that our measurement system, with a maximum measurable power loss of 200 dB, had connected with a probability of 56.2% during the measurement period. Model simulation showed that evaporation duct environments are not ideal in autumn, with an average evaporation duct height (EDH) of 10.6 m. The land breeze in autumn introduced dry and cold air to the link, which could promote evaporation of seawater and reduce PL by approximately 40 dB. Annual spatiotemporal characteristics of EDH showed that evaporation ducts are most suitable for over-the-horizon communication in spring, especially May.

Distribution and ecological health risk assessment of dissolved trace metals in surface and bottom seawater of Yantai offshore, China - Yan Liang; Dawei Pan; Chenchen Wang; Yuxi Lu; Xia Fan (Frontiers in Marine Science, 2022)
The biogeochemical cycle of trace metals plays an important role in the coastal zone. The distribution, interaction, and biogeochemical behavior of dissolved trace metals in surface and bottom seawater are still unclear. This study analyzed the distribution and performed an ecological health risk assessment of dissolved trace metals (Zn, Cd, Co, Pb and Cr) in surface and bottom seawater in the summer (August) of 2019 and 2020 in the seawater of the Yantai offshore area, China. Zinc (Zn), cadmium (Cd), cobalt (Co), lead (Pb) and chromium (Cr) ranged from 23.76–117.47 μg/L (42.67 μg/L ± 15.15), 0.21–0.51 μg/L (0.30 μg/L ± 0.05), 0.90–2.94 μg/L (1.09 μg/L ± 0.31), 0.13–1.06 μg/L (0.39 μg/L ± 0.17), and 2.00–9.9 μg/L (5.38 μg/L ± 2.99) in the summer of the two years. The average metal (Zn and Co) concentrations were slightly higher than the other Chinese coastal areas, while the major contamination pressures were from Zn and Pb. The largest contaminants were in the following order: Zn > Pb > Cd > Cr > Co. Correlation analysis, principal component analysis and hierarchical cluster were used to determine the potential origins and cause the spatial distribution of the multiple dissolved trace metals. The major sources of the trace metal contamination in study area were identified as external inputs from natural human and atmospheric settling and the natural release of the trace metals in sediments under external disturbances. Riverine inputs, the Lubei coastal current and aquaculture significantly influenced the multi-parameter horizontal distributions of the dissolved trace metals and dissolved organic carbon. Although the growth of phytoplankton was strong in summer, the uptake of Zn, Cd, Co and Pb was negligible compared with the exogenous input. The concentrations of Zn, Cd, Co and Pb were higher in the surface than those in the bottom. Monsoons, tides and wind waves also influence the migration, transformation and distribution of dissolved trace metals and dissolved organic carbon. This study provides important information on the biogeochemical cycle process (migration and conversion) and distribution of dissolved trace metals at different depths in coastal and marine pasture areas.

Thermal equation of state of Cr-pyrope: implications for entrapment pressure of Cr-pyrope inclusion in diamond - Jingui Xu; Dawei Fan; Bo Li; Sergey N. Tkachev; Dongzhou Zhang; Guangzhong Yang; Yi Zhou; Jiamei Song; Wenge Zhou (Contributions to Mineralogy and Petrology, 2022)

Equation of state of elbaite at high pressure up to 21.1 GPa and room temperature - Wei Chen; Shijie Huang; Zhilin Ye; Jiamei Song; Shanrong Zhang; Mengzeng Wu; Dawei Fan; Wenge Zhou (Physics and Chemistry of Minerals, 2022)

Biocontrol potential of endophytic Trichoderma citrinoviride HT-1 against root rot of Rheum palmatum through both antagonistic effects and induced systemic resistance - DaWei Chen; QinZheng Hou; BaoLi Fan; Hui Zhang; LingYun Jia; Kun Sun (World Journal of Microbiology and Biotechnology, 2022)

Hyperextended crustal structure of the Qiongdongnan Basin and subsequent magmatic influence from the Hainan mantle plume - Shaohong Xia; Chaoyan Fan; Dawei Wang; Jinghe Cao; Fang Zhao (Science China Earth Sciences, 2022)

Molecular epidemiology of type I and II feline coronavirus from cats with suspected feline infectious peritonitis in China between 2019 and 2021 - Lishan Lin; Dawei Yao; Lei Wu; Rubin Fan; Yang Liu; Zhenlei Zhou (Archives of Virology, 2022)

A chemo-mechanical coupling model for concrete lining subjected to external sulfate attack - Huiming Hou; Dawei Hu; Hui Zhou; Jingjing Lu; Fan Zhang (European Journal of Environmental and Civil Engineering, 2021)

The Effect of Pre-heating Treatment and Water–Cement Ratio on the Shearing Behavior and Permeability of Granite–Cement Interface Samples - Fan Zhang; Tanzhuo Cheng; Zhenzhen Zhu; Dawei Hu; Jianfu Shao (Rock Mechanics and Rock Engineering, 2021)

Gas permeability evolution of granite under confining pressure unloading tests - Dawei Hu; Jun Li; Hui Zhou; Jingjing Lu; Dongdong Ma; Fan Zhang (European Journal of Environmental and Civil Engineering, 2021)

Experimental investigations on the tensile behaviour of granite after heating and water-cooling treatment - Fan Zhang; Cong Dai; Yuhao Zhang; Dianbin Guo; Jianfu Shao; Dawei Hu (Bulletin of Engineering Geology and the Environment, 2021)

Numerical study on strength and failure characteristics of rock samples with different hole defects - Shaojie Chen; Zhiguo Xia; Fan Feng; Dawei Yin (Bulletin of Engineering Geology and the Environment, 2021)

Volunteered Geographic Information Research in the First Decade: Visualizing and Analyzing the Author Connectedness of Selected Journal Articles in GIScience - Yingwei Yan; Dawei Ma; Wei Huang; Chen-Chieh Feng; Hongchao Fan; Yingbin Deng; Jianhui Xu (Journal of Geovisualization and Spatial Analysis, 2020)

Chemical and isotopic constraints on the origin of saline waters from a hot spring in the eastern coastal area of China - Yinlei Hao; Zhonghe Pang; Yanlong Kong; Jiao Tian; Yingchun Wang; Dawei Liao; Yifan Fan (Hydrogeology Journal, 2020)

Metabolite profiling of Huaiyang Medicago polymorpha with different mowing crops - Na Guo; Dawei Yang; Changxi Liu; Han Yan; Xiaofang Yang; Xiaoqin Wang; Bin Fan (Natural Product Research, 2020)

Depositional environments of limestones from the Taiyuan Formation in the North China Block interpreted from REE proxies - Dawei Lv; Wengui Fan; John I. Ejembi; Dun Wu; Dongdong Wang; Zengxue Li; Junpeng Li; Pingping Li (Carbonates and Evaporites, 2020)

Tamarixetin protects against cardiac hypertrophy via inhibiting NFAT and AKT pathway - Cheng Fan; Yuan Li; Hui Yang; Yuqian Cui; Hao Wang; Heng Zhou; Jianning Zhang; Binfeng Du; Qian Zhai; Dawei Wu; Xiaomei Chen; Haipeng Guo (Journal of Molecular Histology, 2019)

Phase transition and thermoelastic behavior of barite-group minerals at high-pressure and high-temperature conditions - Zhilin Ye; Bo Li; Wei Chen; Ruilian Tang; Shijie Huang; Jingui Xu; Dawei Fan; Wenge Zhou; Maining Ma; Hongsen Xie (Physics and Chemistry of Minerals, 2019)

Compressional behavior of natural eclogitic zoisite by synchrotron X-ray single-crystal diffraction to 34 GPa - Jingui Xu; Dongzhou Zhang; Dawei Fan; Xiang Wu; Feng Shi; Wenge Zhou (Physics and Chemistry of Minerals, 2019)

Compressibility and expansivity of anglesite (PbSO4) using in situ synchrotron X-ray diffraction at high-pressure and high-temperature conditions - Bo Li; Jingui Xu; Wei Chen; Zhilin Ye; Shijie Huang; Dawei Fan; Wenge Zhou; Hongsen Xie (Physics and Chemistry of Minerals, 2018)

Thermodynamic properties of San Carlos olivine at high temperature and high pressure - Chang Su; Yonggang Liu; Wei Song; Dawei Fan; Zhigang Wang; Hongfeng Tang (Acta Geochimica, 2018)

Laboratory Investigation on Physical and Mechanical Properties of Granite After Heating and Water-Cooling Treatment - Fan Zhang; Jianjian Zhao; Dawei Hu; Frederic Skoczylas; Jianfu Shao (Rock Mechanics and Rock Engineering, 2018)

Thermoelastic properties of grossular–andradite solid solution at high pressures and temperatures - Dawei Fan; Yunqian Kuang; Jingui Xu; Bo Li; Wenge Zhou; Hongsen Xie (Physics and Chemistry of Minerals, 2017)

Study on Enhanced Dissolution of Azilsartan-Loaded Solid Dispersion, Prepared by Combining Wet Milling and Spray-Drying Technologies - Tianshu Lu; Yinghua Sun; Dawei Ding; Qi Zhang; Rui Fan; Zhonggui He; Jing Wang (AAPS PharmSciTech, 2017)

Anisotropies in Mechanical Behaviour, Thermal Expansion and P-Wave Velocity of Sandstone with Bedding Planes - Hui Zhou; Haitao Liu; Dawei Hu; Fanjie Yang; Jingjing Lu; Fan Zhang (Rock Mechanics and Rock Engineering, 2016)

High-pressure behavior of natural single-crystal epidote and clinozoisite up to 40 GPa - Fei Qin; Xiang Wu; Ying Wang; Dawei Fan; Shan Qin; Ke Yang; Joshua P. Townsend; Steven D. Jacobsen (Physics and Chemistry of Minerals, 2016)

Estimation of the effective thermal properties of cracked rocks - Hui Zhou; Haitao Liu; Dawei Hu; Fan Zhang; Fanjie Yang; Jingjing Lu (European Journal of Environmental and Civil Engineering, 2016)

Thermal equation of state of natural tourmaline at high pressure and temperature - Jingui Xu; Yunqian Kuang; Bo Zhang; Yonggang Liu; Dawei Fan; Xiaodong Li; Hongsen Xie (Physics and Chemistry of Minerals, 2016)

Laboratory Investigations of the Hydro-Mechanical–Chemical Coupling Behaviour of Sandstone in CO2 Storage in Aquifers - Hui Zhou; Dawei Hu; Fan Zhang; Jianfu Shao; Xiating Feng (Rock Mechanics and Rock Engineering, 2016)

High-pressure study of azurite Cu3(CO3)2(OH)2 by synchrotron radiation X-ray diffraction and Raman spectroscopy - Jingui Xu; Yunqian Kuang; Bo Zhang; Yonggang Liu; Dawei Fan; Wenge Zhou; Hongsen Xie (Physics and Chemistry of Minerals, 2015)

Compressibility and equation of state of beryl (Be3Al2Si6O18) by using a diamond anvil cell and in situ synchrotron X-ray diffraction - Dawei Fan; Jingui Xu; Yunqian Kuang; Xiaodong Li; Yanchun Li; Hongsen Xie (Physics and Chemistry of Minerals, 2015)

Regression Analysis of Non-iatrogenic Factors That Determine Adherence to Radiation Therapy - Xiangzhao Bu; Xuemei Fan; Dawei Hao; Lin Guo; Chengjun Wu; Chong Zhou (Cell Biochemistry and Biophysics, 2015)

Compressibility of carbonophosphate bradleyite Na3Mg(CO3)(PO4) by X-ray diffraction and Raman spectroscopy - Jing Gao; Weifeng Huang; Xiang Wu; Dawei Fan; Ziyu Wu; Dingguo Xia; Shan Qin (Physics and Chemistry of Minerals, 2015)

DISC1 Ser704Cys impacts thalamic-prefrontal connectivity - Bing Liu; Lingzhong Fan; Yue Cui; Xiaolong Zhang; Bing Hou; Yonghui Li; Wen Qin; Dawei Wang; Chunshui Yu; Tianzi Jiang (Brain Structure and Function, 2015)

P–V–T equation of state of spessartine–almandine solid solution measured using a diamond anvil cell and in situ synchrotron X-ray diffraction - Dawei Fan; Jingui Xu; Maining Ma; Jing Liu; Hongsen Xie (Physics and Chemistry of Minerals, 2015)

Influence of TLR4 rs1927907 locus polymorphisms on tacrolimus pharmacokinetics in the early stage after liver transplantation - Zhaowen Wang; Shaohan Wu; Dawei Chen; Feng Guo; Lin Zhong; Junwei Fan; Zhihai Peng (European Journal of Clinical Pharmacology, 2014)

Metabolomics reveals stage-specific metabolic pathways of microbial communities in two-stage anaerobic fermentation of corn-stalk - Dawei Yang; Xiaolei Fan; Xiaoshuang Shi; Shujuan Lian; Jiangtao Qiao; Rongbo Guo (Biotechnology Letters, 2014)

Equation of state of adamite up to 11 GPa: a synchrotron X-ray diffraction study - Jingui Xu; Maining Ma; Shuyi Wei; Xianxu Hu; Yonggang Liu; Jing Liu; Dawei Fan; Hongsen Xie (Physics and Chemistry of Minerals, 2014)

High-pressure elastic behavior of Ca4La6(SiO4)6(OH)2 a synthetic rare-earth silicate apatite: a powder X-ray diffraction study up to 9.33 GPa - Dawei Fan; Shuyi Wei; Maining Ma; Zhiqiang Chen; Baosheng Li; Hongsen Xie (Physics and Chemistry of Minerals, 2014)

Expression of RBMX After Spinal Cord Injury in Rats - Jinlong Zhang; Debao Li; Aiguo Shen; Hui Mao; Huricha Jin; Wei Huang; Dawei Xu; Jianbo Fan; Jiajia Chen; Longfei Yang; Zhiming Cui (Journal of Molecular Neuroscience, 2013)

Compressibility and structural properties of jadeite, NaAlSi2O6 at high pressure - Xiuling Wu; Xiaoyu Fan; Fei Qin; Dawei Meng; Xiaoling Zhang; Long Chen; Weiping Liu; Jianping Zheng (Journal of Earth Science, 2013)

Sustained photo-hydrogen production by Chlorella pyrenoidosa without sulfur depletion - Huanyu Wang; Xiaolei Fan; Yanting Zhang; Dawei Yang; Rongbo Guo (Biotechnology Letters, 2011)